PERANAN METODE PEMBELAJARAN YANBU’A DALAM MENINGKATKAN KOMPETENSI MEMBACA AL QURAN SISWA: PERANAN METODE PEMBELAJARAN YANBU’A DALAM MENINGKATKAN KOMPETENSI MEMBACA AL QURAN SISWA - Rini Setyoningsih (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This research examines the role of the Yanbu'a learning method in increasingthe competence in reading the Koran of students at Roushon Fikr Jombang IslamicElementary School. With a phenomnologic qualitative descriptive model, researchers useobservation, documentation and interviews in extracting data by reducing data, displayingdata, and drawing conclusions in data analysis procedures. The results showed the role ofthe Yanbu'a learning method in improving the reading competence of the Quran studentsin the Islamic Elementary School of Roushon Fikr Jombang has changed since using theYanbu'a method. On the contrary, after using the method of learning Yanbu'a the resultsof the achievements of Islamic elementary school students Roushon Fikr Jombangexperienced many changes namely very rapid progress, which meets the standard ofachievement according to their respective classes. To find out the competence of studentsin reading the Koran, there are several tests that must be taken by students of IslamicElementary School Roushon Fikr Jombang, which has been determined by the BranchManager of Muqarabah Yanbu'a. The tests included: Volume Increase Test which wasattended by parents, and a closed Imtihan that was tested by the central penguus tomeasure student learning outcomes after completing volumes 1-7, and observing pureQur'an juz 1-30.